The Influence of Schooling Fields and Family Environment on Interest in Becoming a Teacher - Durinda Puspasari; Dita Rahmawati (Lectura : Jurnal Pendidikan, 2023)
Based on the phenomenon that happened to Surabaya State University students who had implemented the Pengenalan Lapangan Persekolahan (PLP) program, it showed that there was a lack of interest in becoming a teacher. One of the internal factors is teaching experience in the form of the PLP program and the external factor is the family environment. Goal of the study was to analyze the impact of school district (PLP) introduction and home environment on the educational interests of students in administrative education at Surabaya State University. This kind of examination is quantitative using explanatory. The subjects of this research were all students of the Surabaya State University Office Administration Study Program class of 2019 and then had taken PLP courses with a total of 54 people. The instrument used was a questionnaire with a Likert scale of 5. Data analysis techniques include testing for validity also reliability. Classical acceptance tests consist of normality, multicollinearity, also heteroscedasticity tests, and include hypothesis testing using several linear regression tests consisting of t-tests, F-tests, and coefficient-of-squares tests. The outcome of the t-test showed that the introduction of school fields had a positive and significant effect on interest in becoming a teacher, and the family environment had a positive and significant effect on interest in becoming a teacher. The introduction of school fields and family environment has had a positive and significant impact on students’ savor in becoming a teacher in University Office Administration Education students Surabaya Country.